Criminal Liability of Those Who Disseminate Pornographic Content from the Perspective of the Law on Information and Electronic Transactions - Leonaldo Handi Lukito; Ferry Irawan Febriansyah; Yogi Prasetyo (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
The study aims to analyze criminal liability for perpetrators who disseminate intimate content without consent (revenge porn) and to assess the effectiveness of legal protections for victims based on the framework of the Electronic Information and Transactions Law (ITE Law) and Indonesian criminal law. The method employed is normative legal research using a legislative and conceptual approach, supplemented by an examination of relevant law enforcement practices to assess the application of norms and principles of criminal liability. The novelty of this study lies in its critique of the inability of Indonesia’s cybercriminal law regime to classify revenge porn as a consent-based crime. To date, the provisions in the ITE Law have placed greater emphasis on aspects of public decency, and thus have not been fully capable of addressing the harms arising from violations of the victim’s privacy. This study proposes a new normative framework that establishes a violation of consent as the basis for criminal liability, thereby ensuring that the concept of revenge porn is understood not only as a violation of public decency but also as a violation of an individual’s right to privacy and dignity. The findings indicate that although the ITE Law has established a legal basis for criminalizing the dissemination of intimate content without consent, its implementation still faces normative and technical obstacles, such as ambiguous legal provisions, overlapping regulations with the Pornography Law and the Criminal Code, weak digital evidence mechanisms, and insufficient protection for victims who continue to suffer psychological and social harm. The conclusions of this study underscore the need for more specific regulatory updates regarding electronic-based sexual crimes, clarification of legal boundaries within the ITE Law, strengthening of the “right to be forgotten” mechanism, and capacity building for law enforcement officials so that legal protection for victims of revenge porn can be realized more effectively, fairly, and with a focus on the victims’ recovery.